2020
DOI: 10.1016/j.amepre.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Associated Risk Factors, and Characteristics of COVID-19 Among Healthcare Personnel in a Spanish Health Department

Abstract: Introduction This study examines the frequency, associated factors, and characteristics of healthcare personnel coronavirus disease 2019 (COVID-19) cases in a healthcare department that comprises a tertiary hospital and its associated 12 primary healthcare centers. Methods This study included healthcare personnel that showed symptoms or were in contact with a COVID-19 case patient from March 2 to April 19, 2020. Their evolution and characteristics (age, sex, professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
(9 reference statements)
0
12
1
2
Order By: Relevance
“…Among occupational settings, some studies have suggested patients are a more likely source of infection, 2,7 while others have suggested increased occupational exposure risk from other HCP. 5,14 Contrary to the study by Zabarsky et al, HCP in our evaluation were three times more likely to test positive after an exposure to an employee compared to a patient. 15 This is consistent with a study of 5,374 HCP exposures in Minnesota which found that 1.3% of HCP tested positive within 14 days of exposure from a patient source, compared to 3.8% from a HCP source.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Among occupational settings, some studies have suggested patients are a more likely source of infection, 2,7 while others have suggested increased occupational exposure risk from other HCP. 5,14 Contrary to the study by Zabarsky et al, HCP in our evaluation were three times more likely to test positive after an exposure to an employee compared to a patient. 15 This is consistent with a study of 5,374 HCP exposures in Minnesota which found that 1.3% of HCP tested positive within 14 days of exposure from a patient source, compared to 3.8% from a HCP source.…”
Section: Discussioncontrasting
confidence: 99%
“…4 Additionally, a study by Algado-Sellés et al suggested that HCP with confirmed COVID-19 were three times as likely to have a workplace social interaction be the source of infection compared to patient-care related exposures. 5 HCP role may also be a factor. In a cross-sectional serosurvey in Chicago among HCP, nurses were more likely to be seropositive than other HCP.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that N95 and surgical masks were each associated with decreased risk for SARS-CoV-2 infection versus no mask based on unadjusted estimates; an N95 mask was associated with decreased risk versus a surgical mask (OR, 0.76 [CI, 0.63 to 0.92]) ( 18 ). Use of PPE (not limited to masks) was associated with decreased risk for infection versus no PPE in 1 study ( 5 ) (adjusted OR, 0.45 [CI, 0.26 to 0.83]). Two other studies did not find an association between PPE use and risk for infection but reported an imprecise estimate ( 3 ) or did not control for confounders ( 20 ).…”
mentioning
confidence: 99%
“…For this update, 12 cohort studies ( 3–9 , 11 , 14 , 15 , 18 , 19 ) and 6 cross-sectional studies ( 10 , 12 , 13 , 16 , 17 , 20 ) were added ( Supplement Table 1 ). Four studies were done in the United States ( 4 , 7 , 18 , 20 ), 10 in Europe (Spain [ 5 , 11 , 14 ], Italy [ 8 , 9 ], the United Kingdom [ 12 , 17 ], France [ 13 ], Sweden [ 15 ], and the Netherlands [ 15 ]), 2 in India ( 6 , 10 ), and 1 each in China ( 19 ) and Egypt ( 3 ). As with studies included in prior updates, the studies had methodological limitations, including potential recall bias, low or unclear participation rates, small sample sizes, and potential collinearity.…”
mentioning
confidence: 99%
“…However, in their study, physicians had the highest number of positive tests 7 . Algado-Sellés et al reported a COVID-19 prevalence of 4% (95% CI: 3.4–4.6) in Spanish health workers 8 , but they only assessed symptomatic cases; however, they considered that the prevalence would be 4.7–5-3% if they included asymptomatic cases. The aforementioned authors stated that positivity rates were higher due to exposure to patients.…”
Section: Discussionmentioning
confidence: 99%